Forced to care : coercion and caregiving in America - Glenn, Evelyn Nakano (Cambridge, Mass. : Harvard University Press, 2010)
This title looks at the caregiving system in the US and compares it with slavery and other forms of forced labour. The book illuminates the source of contradictions between American beliefs about the value and importance of caring in a good society and the exploitation and devalued status of those who do the caring.
Who cares? -- Caring for one's own and caring for a living -- The movement to reform women's caring -- From moral duty to legal obligation -- Paid caring in the home -- Neoliberalism and globalization -- Creating a caring society.
Includes bibliographical references and index.
Keywords: Caregivers -- United States